2011
DOI: 10.1128/mcb.01403-10
|View full text |Cite
|
Sign up to set email alerts
|

Talin1 Regulates Integrin Turnover To Promote Embryonic Epithelial Morphogenesis

Abstract: Talin is a cytoskeletal protein that binds to integrin ␤ cytoplasmic tails and regulates integrin activation. Talin1 ablation in mice disrupts gastrulation and causes embryonic lethality. However, the role of talin in mammalian epithelial morphogenesis is poorly understood. Here we demonstrate that embryoid bodies (EBs) differentiated from talin1-null embryonic stem cells are defective in integrin adhesion complex assembly, epiblast elongation, and lineage differentiation. These defects are accompanied by a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 49 publications
5
34
0
Order By: Relevance
“…Support for this hypothesis comes from our previous studies (17) where we showed that deletion of the Tln1 gene in CMs led to increased levels of β1D integrin. Likewise, work in other cell types has shown that Tln controls β1-integrin expression at the cell membrane (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Support for this hypothesis comes from our previous studies (17) where we showed that deletion of the Tln1 gene in CMs led to increased levels of β1D integrin. Likewise, work in other cell types has shown that Tln controls β1-integrin expression at the cell membrane (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…18S RNA was used as a loading control as described previously. 47 Statistical analysis. Statistical analysis was performed using SigmaStat software (Systat Software, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…• Experimental studies (Delcommenne & Streuli, 1995;Davis et al, 2001;Liu et al, 2011;Lobert et al, 2010) have shown that the half-lifes of the integrins range from 0.04 − 4 days. This corre- Table 2, of (a) Cancer cell density u 1 of the first ("normal") population; (b) Cancer cell density u 2 of the second ("mutant") population; (c) ECM density f ; (d) Integrin density c.…”
Section: Summary Of Model Variables and Parametersmentioning
confidence: 99%